TTL-Expression Modulates Epithelial Morphogenesis - Müller, Manuel; Ringer, Karina; Hub, Florian; Kamm, Natalia; Worzfeld, Thomas; Jacob, Ralf (Frontiers in Cell and Developmental Biology, 2021)
Epithelial monolayer formation depends on the architecture and composition of the microtubule cytoskeleton. Microtubules control bidirectional trafficking and determine the positioning of structural cellular proteins. We studied the role of tubulin tyrosination in epithelial cell shape and motility. Tubulin tyrosine ligase (TTL), the enzyme that adds tyrosine to the carboxy terminus of detyrosinated α-tubulin, was depleted or overexpressed in 2D epithelial monolayers as well as in 3D intestinal organoids. We demonstrate qualitatively and quantitatively that in the absence of TTL the cells comprise high levels of detyrosinated tubulin, change their shape into an initial flat morphology and retardedly acquire a differentiated columnar epithelial cell shape. Enhanced adhesion and accelerated migration patterns of TTL-knockout cells combined with reverse effects in TTL-overexpressing cells indicate that the loss of TTL affects the organization of cell adhesion foci. Precipitation of detyrosinated tubulin with focal adhesion scaffold components coincides with increased quantities and persistence of focal adhesion plaques. Our results indicate that the equilibrium between microtubules enriched in detyrosinated or tyrosinated tubulin modulates epithelial tissue formation, cell morphology, and adhesion.